2023
DOI: 10.1177/23259671231160738
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Clinical Outcomes After Arthroscopic Rotator Cuff Repair

Abstract: Background: Limited knowledge exists regarding prognostic factors after rotator cuff repair. Purpose: To identify pre- and perioperative predictors for functional outcomes after arthroscopic rotator cuff repair. Study Design: Case-control study; Level of evidence, 3. Methods: This study included patients who underwent arthroscopic rotator cuff repair between January 2013 and April 2019 and who had preoperative magnetic resonance imaging scans. The procedures were performed by 4 shoulder surgeons at a single in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Nicholson et al [ 20 ] reported that smoking was the only factor significantly adversely influencing patient-reported outcomes. Malavolta et al [ 21 ] did not find that smoking affected clinical results. This was probably due to the inclusion criteria used in their study for determining a patient as a smoker which grouped former smokers and active smokers together as opposed to only active smokers in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Nicholson et al [ 20 ] reported that smoking was the only factor significantly adversely influencing patient-reported outcomes. Malavolta et al [ 21 ] did not find that smoking affected clinical results. This was probably due to the inclusion criteria used in their study for determining a patient as a smoker which grouped former smokers and active smokers together as opposed to only active smokers in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…RC syndrome is one of the common problems in orthopaedics and traumatology, with a growing global incidence [4,10]. Factors such as age, comorbid diseases, activity levels, and smoking are among the known risk factors for RC tears [4].…”
Section: Discussionmentioning
confidence: 99%
“…Although various tests are used to determine the progression of patients following a rotator cuff repair, the American Shoulder and Elbow Surgeons Shoulder (ASES) [ 13 , 14 , 15 ] and Constant–Murley shoulder (CMS) [ 16 ] scores are common patient self-evaluations used to determine functional ability. Malavolta et al [ 17 ] previously reported that the ASES is a good prognostic tool for use at the 6-, 12-, and 24-month postoperative periods after supraspinatus repair. Similarly, the CMS has been reported to correlate with the isokinetic evaluation of the external rotation strength at the 6- and 12-month post-operative periods for rotator cuff repair [ 18 ].…”
Section: Introductionmentioning
confidence: 99%